Molar incisor hypomineralization and its association with dental caries: A systematic review and meta-analysis (Research, Society and Development, 2025)
Objective: To investigate, through a thorough analysis of the literature, the association between MIH and the increased risk of dental caries in children, discussing the related factors and the indicated treatments. Methodology: A systematic review of the literature was conducted through the analysis of studies retrieved from the EMBASE, PubMed, LILACS, and Scopus databases, using the descriptors “Molar Hypomineralization Dental,” “Molar Incisor Hypomineralization,” “Dental Caries,” and “Pediatric Dentistry.” Results: Children with MIH are 3.69 times more likely (95% CI: 2.81–4.84) to develop caries experience compared to those without this condition. The heterogeneity among studies was significant, as demonstrated by the test (I² = 79.1%; p < 0.001). Conclusion: The positive association between MIH and dental caries, evidenced in this study, may be related to the hypomineralized and more porous enamel structure, which favors biofilm retention and bacterial penetration, highlighting the importance of early diagnosis and appropriate intervention in MIH cases.